Potencial probiótico in vitro e in vivo de Lactobacillus plantarum B7 e Lactobacillus rhamnosus D1 contra Listeria monocytogenes na infecção experimental e produção de leite fermentado de cabra - Gustavo Lucas Costa Valente (2018)
Lactobacillus spp. are lactic acid bacteria with important implications in food industry due to their fermentation capacities. Some strains may also contribute to the balance of the intestinal microbiota and to the health of the host when administered in an adequade concentration, characterizing a probiotic potential. Among the health benefits, there are protections against infectious agents due to mechanisms like: nutrient competition, competitive exclusion, direct antagonism, immuno and inflammatory modulation. On the other hand, Listeria monocytogenes is a pathogen often transmitted by foods of animal origin and is related to the occurrence of enteropathy, meningoencephalitis, abortion and septicemia. The aim of this survey was to evaluate the in vitro and in vivo probiotic potential of Lactobacillus plantarum B7 and Lactobacillus rhamnosus D1, isolated from Minas artesanal cheese of the Serra da Canastra, against L. monocytogenes. It was still intended to develop a potentially functional fermented goat milk with B7 and D1, and to evaluate the physical-chemical, microbiological and sensorial quality during 30 days of storage at 7 ° C. Both strains demonstrated in vitro inhibitory activity against L. monocytogenes, besides showing sensitivity to antimicrobials and resistance to gastric acids and bile salts. In the in vivo assays, using conventional mice of BALB/c strain to determination of mortality rate and weight gain, no differences were observed (p>0.05) between the mortality rate of the control, B7 and D1 groups after experimental infection by L. monocytogenes. However, the group treated with D1 showed a higher weight gain (p<0.05) than other groups. The goat fermented milks by B7, D1, both and Lactobacillus casei YA showed physicochemical parameters adequate to the legislation and scientific studies of reference. Microbiological standards have demonstrated the safety of the product and an adequate population of Lactobacillus spp. (> 108 CFU/g) throughout the 30-day storage period at 7 °C. In the sensory analyses, D1 milk fermented demonstred higher consumer acceptance and purchase intention (p<0.05) than other treatments. These results indicate that D1 showed probiotic potential and may be carried out by fermented goat milk.